Overcoming the limits of institutional reform in Uganda - Matt Andrews; Lawrence Bategeka (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2013)
This paper begins by noting that Uganda has been a public sector reform leader in Africa. It has pursued reforms actively and consistently for three decades now, and has produced many laws, processes and structures that are 'best in class' in Africa (and beyond). The problem is that many of the reforms have been limited to these kinds of gains - producing new institutional forms that function poorly and yield limited impacts. Various kinds of data showed - in various areas (civil service and public administration, public financial management, revenue management, procurement, and anti-corruption) - that laws are often not being implemented, processes are being poorly executed, and there is insufficient follow-up to make sure that new mechanisms work as intended. The paper suggests that government should reframe its reform agenda to address these limitations and close the gaps between what Uganda's system looks like and how it functions.
Keywords: H11; O10; O19; 330; development; Uganda; reform; growth; governance; Africa